Preparation method and application of composite bipolar plate
By doping carbon nanotubes in a fluidized bed reactor, and preheating, premixing and molding with other conductive fillers and thermoplastics, composite bipolar plates with high conductivity and mechanical strength are prepared, which solves the problems of high cost, poor reliability and uneven conductivity of existing liquid flow battery bipolar plates, and achieves high-performance bipolar plates suitable for industrial production.
Patent Information
- Application Number
- CN202510373643.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The sealing method of existing flow battery bipolar plates is high in cost and has poor reliability, and the compatibility between conductive carbon materials and resin substrates is poor, resulting in uneven conductivity and reduced welding reliability.
By doping the carbon nanotubes into a fluidized bed reactor, and preheating, premixing and molding with zero-dimensional and two-dimensional conductive fillers and thermoplastics, composite bipolar plates with excellent conductivity and mechanical strength were prepared.
The high conductivity (150~185S/cm) and mechanical strength (20.9~28.3MPa tensile strength, 40.2~55.7MPa bending strength) of the composite bipolar plate is achieved, which is suitable for industrial production and can be applied to liquid flow battery stacks through laser welding.
Smart Images

Figure CN119890342A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of liquid flow batteries, and in particular relates to a preparation method and application of a composite bipolar plate. Background Art
[0002] Liquid flow battery is a new type of large-capacity energy storage battery that has emerged in recent years. It consists of a stack unit, electrolyte, electrolyte storage and supply unit, and management control unit. It is a high-performance battery that separates the positive and negative electrolytes and circulates them separately. With the construction and popularization of photovoltaic power stations and wind power stations, high-capacity, high-safety, and long-life liquid flow battery energy storage systems are highly praised by everyone. As a key material for liquid flow battery stacks, bipolar plates play the role of supporting electrodes and collecting current in liquid flow battery stacks.
[0003] At present, the industry generally adopts the method of stacking single-piece batteries to assemble liquid flow battery stacks. The single-piece batteries are sealed by sealing rings, hot melt adhesive films, self-sealing, etc. to achieve the overall sealing of the stack. However, this assembly method has high sealing cost and poor reliability. The rubber is prone to electrolyte leakage after aging, and the sealing ring is also prone to aging and cracking in the long-term use of the pressed state, causing electrolyte leakage. The bipolar plate substrate used in the above-mentioned traditional sealing method is usually a thermosetting resin, which plays the role of filling the pores of the carbon material. Due to the small amount of thermosetting resin added, long-term use in the liquid flow battery electrolyte will cause the bipolar plate to swell, and then cause the positive and negative electrolytes to mix, affecting the normal operation of the liquid flow battery. At present, the emerging stack sealing method is laser welding, that is, the bipolar plate based on thermoplastic resin is laser welded with the electrode frame to achieve the overall sealing of the stack, thereby avoiding the use of seals, saving costs and slowing down the corrosion of the electrolyte. However, ordinary conductive carbon materials have poor compatibility with resin substrates, resulting in uneven mixing of the composition. The conductivity of the pressed bipolar plates is uneven and poor, which inevitably requires increasing the amount of conductive carbon material added. However, excessive addition of conductive carbon material will reduce the reliability of welding and cannot meet the needs of high conductivity and weldability at the same time.
[0004] A Chinese patent document with publication number CN118996487A discloses a method for preparing a nitrogen-doped multi-walled carbon nanotube-loaded metal Cr electrocatalytic material, in which the carbon nanotubes are subjected to high-temperature calcination to achieve nitrogen doping, but the nitrogen doping process time of this method is too long and the efficiency is low; a Chinese patent document with publication number CN114497614A discloses a composite bipolar plate for a liquid flow battery and a method for preparing the same, in which the bipolar plate is prepared by partitioning, the middle area is highly conductive, and the edge area is weldable, but due to the poor compatibility of ordinary conductive carbon materials with the resin substrate, the connectivity between the conductive area and the transition area and the insulating area is poor, and the mechanical properties of the connecting part are poor, making it unsuitable for industrial production. Summary of the invention
[0005] The present invention provides a preparation method and application of a composite bipolar plate. The preparation method provided by the present invention is simple, has a short reaction time, and a high reaction efficiency. The formed bipolar plate can be applied to the assembly of a liquid flow battery stack by laser welding, has excellent electrical conductivity and mechanical strength, and is easy to industrialize.
[0006] To solve the above technical problems, the present invention comprises the following steps: (1) adding carbon nanotubes to concentrated nitric acid whose mass is 5 to 10 times of the mass of carbon nanotubes, treating at a temperature of 70 to 90°C for 1 to 3 hours, pouring into ice water for quenching, filtering, washing with water until neutral, and vacuum drying to obtain carbon nanotube powder; (2) The carbon nanotube powder obtained in step (1) is loaded into a fluidized bed reactor, nitrogen is introduced, the temperature is raised to 700-800° C., ammonia is introduced, and the pressure in the reactor is maintained to react for 8-10 minutes to obtain nitrogen-doped carbon nanotube powder; (3) preheating and premixing the nitrogen-doped carbon nanotube powder obtained in step (2) with a zero-dimensional conductive filler, a two-dimensional conductive filler and a thermoplastic plastic in an air flow dryer to obtain a premixed composition, wherein the premixed composition is the nitrogen-doped carbon nanotubes; (4) The premixed composition obtained in step (3) is compression molded to obtain a composite bipolar plate.
[0007] Preferably, the ammonia flow rate in step (2) is 3-4 m 3 / min, and the pressure inside the reactor is 2~4MPa.
[0008] Preferably, in step (3), the zero-dimensional conductive filler is acetylene black or ketjen black; the two-dimensional conductive filler is graphene or flake graphite; the thermoplastic is one of high-density polyethylene, polypropylene or polyvinylidene fluoride. The ratio of the added amount of the zero-dimensional conductive filler, the nitrogen-doped carbon nanotube powder and the two-dimensional conductive filler is 1:1.5~4:0.5~2; the mass ratio of the sum of the mass of the zero-dimensional conductive filler and the two-dimensional conductive filler to the mass of the thermoplastic is 1:0.4~0.7.
[0009] Preferably, in step (3), the operating temperature of the air flow dryer is 100-170° C., and the operating time is 15-30 seconds.
[0010] Another technical solution provided by the present invention is to use the prepared composite bipolar plate in a liquid flow battery.
[0011] Compared with the prior art, the present invention has the following advantages: (1) The technical solution of the composite bipolar plate preparation method provided by the present invention is to use a fluidized bed reactor to nitrogen-dope carbon nanotubes under high temperature and high pressure conditions. Compared with the traditional tubular furnace reaction, the materials in the fluidized bed reactor are in a suspended fluidized state. During the process of introducing ammonia gas, the contact area between the two can be increased, the doping reaction is faster, and the reaction efficiency is higher; (2) The technical solution of the composite bipolar plate preparation method provided by the present invention is to nitrogen-dope the carbon nanotubes. The nitrogen-doping temperature is controlled at a high temperature of 700-800°C to free the unstable groups on the surface of the carbon nanotubes and introduce stable -NH 2 , so that the bipolar plate obtained has higher conductivity and better mechanical properties; the presence of surface groups also enhances the dispersion of carbon nanotubes, thereby improving their interfacial compatibility with polymer resins, making the conductivity of the bipolar plate obtained more uniform; (3) The present invention uses nitrogen-doped carbon nanotubes as one-dimensional conductive fillers, and then adds zero-dimensional and two-dimensional conductive fillers respectively, so that the three conductive fillers cooperate with each other to form a conductive network, thereby improving conductivity; (4) The present invention utilizes an airflow dryer to simultaneously preheat and premix the composition, completing the process in one step in a relatively short period of time. The composition can be fully mixed and quickly preheated in an airflow environment. Compared with the traditional bipolar plate preparation method, the material mixing time is saved; the airflow dryer can also remove a small amount of water contained in the premixed composition in a relatively short period of time, which helps to reduce defects in the bipolar plate and improve mechanical properties; (5) Compared with the traditional production process, the reaction time of the present invention is shorter, and the prepared bipolar plate can not only be welded, but also has excellent electrical conductivity and mechanical strength, and is easy to industrialize. The electrical conductivity of the composite bipolar plate can reach 150~185S / cm, the tensile strength can reach 20.9~28.3MPa, and the bending strength can reach 40.2~55.7MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is an X-ray photoelectron spectroscopy (XPS) spectrum of nitrogen-doped carbon nanotubes; wherein, a is the full XPS spectrum of nitrogen-doped carbon nanotubes, and b is the N1s spectrum of nitrogen-doped carbon nanotubes; Figure 2 The following are scanning electron microscope (SEM) and scanning electron microscope energy spectrum (EDS) images of Example 1. DETAILED DESCRIPTION
[0013] The present invention is further described below in conjunction with specific embodiments, but is not limited thereto. At the same time, the experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials described are all commercially available products unless otherwise specified. In the following embodiments of the present invention, the fluidized bed reactor used is: a gas-solid phase fluidized bed reactor; the airflow dryer used is: a cyclone airflow dryer, all of which are within the scope of the prior art. Example 1
[0014] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 80°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 1 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 700°C, ammonia is introduced at a flow rate of 4 m³ / min, and the pressure in the reactor is maintained at 3 MPa. After reacting for 10 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 2.412 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 1.608 g of acetylene black, 1.608 g of graphene, and 2.412 g of polypropylene, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 170° C. for 15 seconds. After the preheating and premixing is completed, 8.04 g of the premixed composition is obtained.
[0015] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 200° C. for molding, and pressed at a pressure of 20 MPa for 10 min. After the pressing is completed, it is cooled in a water bath to obtain a composite bipolar plate.
[0016] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 30 W and a laser operating speed of 200 mm / min. Example 2
[0017] (1) Add 1000 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 70°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 2 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 95.1 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 750°C, ammonia is introduced at a flow rate of 3 m³ / min, and the pressure in the reactor is maintained at 4 MPa. After reacting for 8 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 4.272 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 1.068 g of Ketjen black, 1.068 g of flake graphite, and 4.272 g of polyvinylidene fluoride, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 150° C. for 30 seconds. After the preheating and premixing is completed, 10.68 g of a premixed composition is obtained.
[0018] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 180° C. and pressed at a pressure of 15 MPa for 12 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0019] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 35 W and a laser operating rate of 100 mm / min. Example 3
[0020] (1) Add 1000 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 90°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 3 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 95.1 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 800°C, ammonia is introduced at a flow rate of 3.5 m³ / min, and the pressure in the reactor is maintained at 2 MPa. After reacting for 9 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.204 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 2.136 g of acetylene black, 1.602 g of flake graphite, and 3.738 g of polyvinylidene fluoride, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 150° C. for 20 seconds. After the preheating and premixing is completed, 10.68 g of a premixed composition is obtained.
[0021] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 180° C. and pressed at a pressure of 17 MPa for 15 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0022] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame, with a laser power of 33 W and a laser operating rate of 150 mm / min. Example 4
[0023] (1) Add 750 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 80°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 2 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 96.7 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 800°C, ammonia is introduced at a flow rate of 4 m³ / min, and the pressure in the reactor is maintained at 4 MPa. After reacting for 9 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 2.814 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 1.206 g of Ketjen black, 1.608 g of graphene, and 2.412 g of high-density polyethylene, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 100° C. for 30 seconds. After the preheating and premixing is completed, 8.04 g of the premixed composition is obtained.
[0024] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 160° C. and pressed at a pressure of 17 MPa for 10 min. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0025] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 30 W and a laser operating rate of 100 mm / min. Example 5
[0026] (1) Add 750 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 90°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 1 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 96.7 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 700° C., ammonia is introduced at a flow rate of 3.5 m³ / min, and the pressure in the reactor is maintained at 2 MPa. After reacting for 10 min, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.216 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 0.804 g of acetylene black, 1.206 g of flake graphite, and 2.814 g of polypropylene, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 170° C. for 20 seconds. After the preheating and premixing is completed, 8.04 g of a premixed composition is obtained.
[0027] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 200° C. for molding, and pressed at a pressure of 15 MPa for 15 minutes. After the pressing is completed, it is cooled in a water bath to obtain a composite bipolar plate.
[0028] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame, with a laser power of 33 W and a laser operating rate of 150 mm / min. Example 6
[0029] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 80°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 3 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 750°C, ammonia is introduced at a flow rate of 3 m³ / min, and the pressure in the reactor is maintained at 3 MPa. After reacting for 8 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.216 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 1.608 g of Ketjen black, 0.804 g of graphene, and 3.216 g of high-density polyethylene, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 100° C. for 15 seconds. After the preheating and premixing is completed, 8.04 g of the premixed composition is obtained.
[0030] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 160° C. and pressed at a pressure of 20 MPa for 12 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0031] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 35 W and a laser operating rate of 200 mm / min. Comparative Example 1
[0032] (1) Weigh 2.412 g of carbon nanotubes, 1.608 g of acetylene black, 1.608 g of graphene, and 2.412 g of polypropylene, respectively, and premix the above four fillers in a high-speed mixer for 15 seconds to obtain 8.04 g of a premixed composition.
[0033] (2) The premixed composition obtained in step (1) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 190° C. and pressed at a pressure of 20 MPa for 10 min. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0034] (3) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 30 W and a laser operating speed of 200 mm / min. Comparative Example 2
[0035] (1) Weigh 2.412 g of carbon nanotubes, 1.608 g of acetylene black, 1.608 g of graphene, and 2.412 g of polypropylene, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 170° C. for 15 seconds. After the preheating and premixing is completed, 8.04 g of the premixed composition is obtained.
[0036] (2) The premixed composition obtained in step (1) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 190° C. and pressed at a pressure of 20 MPa for 10 min. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0037] (3) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 30 W and a laser operating speed of 200 mm / min. Comparative Example 3
[0038] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 80°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 2 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 750°C, ammonia is introduced at a flow rate of 3 m³ / min, and the pressure in the reactor is maintained at 4 MPa. After reacting for 8 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 4.272 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 1.068 g of Ketjen black, 1.068 g of flake graphite, and 4.272 g of polyvinylidene fluoride, respectively, and premix the above four fillers in a high-speed mixer for 30 seconds to obtain 10.68 g of a premixed composition.
[0039] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 200° C. and pressed at a pressure of 15 MPa for 12 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0040] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame at a laser power of 35 W and a laser operating rate of 100 mm / min. Comparative Example 4
[0041] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 90°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 3 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a tubular furnace, and nitrogen is continuously introduced. After the temperature of the tubular furnace is raised to 800°C, ammonia is introduced at a flow rate of 3.5 m³ / min. After reacting for 9 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.204 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 2.136 g of acetylene black, 1.602 g of flake graphite, and 3.738 g of polyvinylidene fluoride, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 150° C. for 20 seconds. After the preheating and premixing is completed, 10.68 g of a premixed composition is obtained.
[0042] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 180° C. and pressed at a pressure of 17 MPa for 15 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0043] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame, with a laser power of 33 W and a laser operating rate of 150 mm / min. Comparative Example 5
[0044] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 90°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 3 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 600° C., ammonia is introduced at a flow rate of 3.5 m³ / min, and the pressure in the reactor is maintained at 2 MPa. After reacting for 9 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.204 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 2.136 g of acetylene black, 1.602 g of flake graphite, and 3.738 g of polyvinylidene fluoride, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 150° C. for 20 seconds. After the preheating and premixing is completed, 10.68 g of a premixed composition is obtained.
[0045] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 180° C. and pressed at a pressure of 17 MPa for 15 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0046] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame, with a laser power of 33 W and a laser operating rate of 150 mm / min. Comparative Example 6
[0047] (1) Add 500 g of concentrated nitric acid into a 3 L three-necked flask and stir, heat in a water bath to 90°C, add 100 g of carbon nanotubes into the concentrated nitric acid and stir for 3 h. After the reaction is completed, pour the reactant into ice water to quench, filter with a Buchner funnel, wash with water until neutral, recover the mother liquor, and dry the filter cake in a vacuum oven at 120°C to obtain 98.3 g of carbon nanotube powder; (2) The carbon nanotube powder obtained in (1) is loaded into a fluidized bed reactor, and nitrogen is continuously introduced. After the temperature of the fluidized bed reactor is raised to 1000° C., ammonia is introduced at a flow rate of 3.5 m³ / min, and the pressure in the reactor is maintained at 2 MPa. After reacting for 9 minutes, nitrogen-doped carbon nanotube powder is obtained; (3) Weigh 3.204 g of the nitrogen-doped carbon nanotube powder obtained in step (2), 2.136 g of acetylene black, 1.602 g of flake graphite, and 3.738 g of polyvinylidene fluoride, respectively, and preheat and premix the above four fillers in an air flow dryer at a temperature of 150° C. for 20 seconds. After the preheating and premixing is completed, 10.68 g of a premixed composition is obtained.
[0048] (4) The premixed composition obtained in step (3) is filled into a mold with a size of 10 cm×10 cm×0.5 mm, and then the mold is placed in a hydraulic press preheated to 180° C. and pressed at a pressure of 17 MPa for 15 minutes. After the pressing is completed, the composite bipolar plate is cooled in a water bath to obtain the composite bipolar plate.
[0049] (5) The composite bipolar plate obtained in step (4) is laser welded to the electrode frame, with a laser power of 33 W and a laser operating rate of 150 mm / min.
[0050]
[0051] Table 1 is the experimental analysis data of the embodiments and comparative examples of this patent. By comparing comparative examples 1 and 2 with embodiment 1, it can be seen that the bipolar plates prepared from nitrogen-doped carbon nanotubes have greatly improved conductivity and mechanical properties, and the mechanical properties and conductivity are higher. This is because the nitrogen-doped carbon nanotubes have better compatibility with thermoplastics, making the connection between carbon and resin tighter and closer; and because the nitrogen-doped carbon nanotubes introduce nitrogen atoms, not only the carbon nanotubes are better dispersed, forming an effective conductive network with conductive fillers at different latitudes, but also the electron transfer of the carbon nanotubes is accelerated, and the conductivity is better, so that the obtained bipolar plate has better conductivity and greatly improved conductivity.
[0052] By comparing Comparative Example 3 with Example 2, it can be seen that the use of an air flow dryer can also improve the conductivity and mechanical properties of the prepared bipolar plate. This is because the air flow dryer allows the composition to be preheated and premixed in a dispersed state, and can quickly and efficiently remove moisture from the composition. The bipolar plate thus pressed has fewer defects, higher mechanical properties, faster electron transfer rate, and higher conductivity.
[0053] From the comparison between Comparative Example 4 and Example 3, it can be seen that the conventional tube furnace high temperature calcination cannot make the carbon nanotubes have a high nitrogen doping degree in a short time, so the bipolar plate prepared in this way has poor conductivity and mechanical properties.
[0054] By comparing Comparative Examples 5 and 6 with Example 3, it can be seen that when the temperature of the fluidized bed reactor is too low or too high, the conductivity and mechanical properties of the bipolar plate will be affected. This is because if the temperature is too low, the nitrogen doping degree of the carbon nanotubes will be low, while if the temperature is too high, the nitrogen-containing groups on the carbon nanotubes will be free and fall off, thereby reducing the conductivity and mechanical properties of the bipolar plate.
[0055] The elemental composition of the nitrogen-doped carbon nanotubes prepared in Example 1 was characterized by X-ray photoelectron spectroscopy (XPS). Figure 1 shown. Figure 1 a is the full XPS spectrum of nitrogen-doped carbon nanotubes, and the peaks at 284 eV, 399 eV, and 531 eV represent the carbon peak, nitrogen peak, and oxygen peak of nitrogen-doped carbon nanotubes, respectively. Figure 1 b is the N1s spectrum of nitrogen-doped carbon nanotubes. The N1s peak was analyzed by peak separation, and the peaks at 398.8eV, 399.5eV and 401.2eV were attributed to pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen, respectively, which shows that nitrogen atoms are doped into the lattice of carbon nanotubes. The doped nitrogen atoms will change the electronic structure of the carbon material at the nitrogen-doped site, which is conducive to electron transmission and can effectively improve the electrical properties of nitrogen-doped carbon nanotubes.
[0056] The surface morphology and element distribution of the composite bipolar plate prepared in Example 1 were analyzed by scanning electron microscopy (SEM) and scanning electron microscopy energy spectrum (EDS). The results are as follows: Figure 2 As shown. It can be seen that the surface of the composite bipolar plate is relatively uniform as a whole, and no obvious distribution of carbon materials is observed. At the same time, the composite bipolar plate was subjected to EDS surface scanning, and it was found that the C element and the F element were evenly distributed, proving that after preheating and premixing in the air flow dryer, the mixture was dispersed more evenly, and there was no obvious agglomeration of carbon materials and polymers. It can be seen from the EDS surface scanning that the C element is obviously distributed on the surface of the composite bipolar plate, proving that there is a connected conductive network on the surface of the composite bipolar plate, which shows a higher conductivity.
Claims
1. A method for preparing a composite bipolar plate, characterized in that: The following steps are involved: (1) adding carbon nanotubes to concentrated nitric acid whose mass is 5 to 10 times of the mass of carbon nanotubes, treating at a temperature of 70 to 90°C for 1 to 3 hours, pouring into ice water for quenching, filtering, washing with water until neutral, and vacuum drying to obtain carbon nanotube powder; (2) The carbon nanotube powder obtained in step (1) is loaded into a fluidized bed reactor, nitrogen is introduced, the temperature is raised to 700-800° C., ammonia is introduced, and the pressure in the reactor is maintained to react for 8-10 minutes to obtain nitrogen-doped carbon nanotube powder; (3) preheating and premixing the nitrogen-doped carbon nanotube powder obtained in step (2) with a zero-dimensional conductive filler, a two-dimensional conductive filler and a thermoplastic plastic in an air flow dryer to obtain a premixed composition; (4) The premixed composition obtained in step (3) is compression molded to obtain a composite bipolar plate.
2. The method for preparing a composite bipolar plate according to claim 1, characterized in that: In the step (2), the ammonia flow rate is 3-4 m 3 / min, and the pressure inside the reactor is 2~4MPa.
3. The method for preparing a composite bipolar plate according to claim 2, characterized in that: In the step (3), the zero-dimensional conductive filler is acetylene black or Ketjen black; the two-dimensional conductive filler is graphene or flake graphite; the thermoplastic plastic is one of high-density polyethylene, polypropylene or polyvinylidene fluoride; the mass ratio of the zero-dimensional conductive filler, the nitrogen-doped carbon nanotube powder and the two-dimensional conductive filler is 1:1.5~4:0.5~2; The mass ratio of the sum of the mass of the zero-dimensional conductive filler and the two-dimensional conductive filler to the mass of the thermoplastic is 1:0.4~0.
7.
4. The method for preparing a composite bipolar plate according to claim 1, characterized in that: In the step (3), the working temperature of the air flow dryer is 100-170°C, and the working time is 15-30s.
5. Application of the composite bipolar plate prepared by the method according to any one of claims 1 to 4, characterized in that: The composite bipolar plate is used in a liquid flow battery.
Citation Information
Patent Citations
Nitrogen-doped carbon nanotube and preparation method thereof
CN104030265A
Carbon nanotube composite lead carbon battery negative electrode plate and preparation method
CN108598366A
Preparation method of nitrogen-doped carbon nanotube conductive paste for lithium ion battery
CN115020029A
Weldable bipolar plate for flow battery as well as preparation method and application of weldable bipolar plate
CN115548363A
Carboaceous nanomaterail and method of preparing the same
KR1020120087402A
Cited By
A method for preparing a composite bipolar plate
CN122576242A